Proliferating borders and precarious queers: migrant justice organising beyond LGBT inclusion. (2018) - Wright, Cynthia
LGBT refugees have rapidly moved up the agenda of the mainstream LGBT movement in Canada and many states in the global North. Yet, the goal of LGBT refugee rights and inclusion in the nation has emerged at a conjuncture in which many states are systematically restricting spaces of asylum and mobility, introducing deeper precarity, surveillance, detention, and border violence in migrant lives. With proliferating borders, the growth of 'irregular' crossings and 'illegalised' people, what strategies might challenge state violence, controls on mobility, and the migrant/refugee binary? Drawing on recent literature on migrant precarity and non-citizenship in Canada, this essay reflects on migrant justice organising, including the self-organising of failed claimants and migrants, in the context of Canadian cities. It concludes with a call for a no border politics that can re-orient a queer politics of migration.